The effects of empagliflozin, dietary energy restriction, or both on appetite‐regulatory gut peptides in individuals with type 2 diabetes and overweight or obesity: The SEESAW randomized, double‐blind, placebo‐controlled trial. Issue 8 (13th May 2022) - Sargeant, Jack A.; King, James A.; Yates, Thomas; Redman, Emma L.; Bodicoat, Danielle H.; Chatterjee, Sudesna; Edwardson, Charlotte L.; Gray, Laura J.; Poulin, Benoit; Waheed, Ghazala; Waller, Helen L.; Webb, David R.; et al.
Abstract: Aim: To assess the impact of the sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor empagliflozin (25 mg once‐daily), dietary energy restriction, or both combined, on circulating appetite‐regulatory peptides in people with type 2 diabetes (T2D) and overweight or obesity. Materials and Methods: In a double‐blind, placebo‐controlled trial, 68 adults (aged 30‐75 years) with T2D (drug naïve or on metformin monotherapy; HbA1c 6.0%‐10.0% [42‐86 mmol/mol]) and body mass index of 25 kg/m 2 or higher were randomized to (a) placebo only, (b) placebo plus diet, (c) empagliflozin only or (d) empagliflozin plus diet for 24 weeks. Dietary energy restriction matched the estimated energy deficit elicited by SGLT2 inhibitor therapy through urinary glucose excretion ( 360 kcal/day). The primary outcome was change in postprandial circulating total peptide‐YY (PYY) during a 3‐hour mixed‐meal tolerance test from baseline to 24 weeks. Postprandial total glucagon‐like peptide‐1 (GLP‐1), acylated ghrelin and subjective appetite perceptions formed secondary outcomes, along with other key components of energy balance. Results: The mean weight loss in each group at 24 weeks was 0.44, 1.91, 2.22 and 5.74 kg, respectively. The change from baseline to 24 weeks in postprandial total PYY was similar between experimental groups and placebo only (mean difference [95% CI]: −8.6 [−28.6 to 11.4], 13.4 [−6.1 to 33.0] and 1.0 [−18.0 to 19.9] pg/ml in placebo‐plus diet, empagliflozin‐only and empagliflozin‐plus‐diet groups, respectively [all P ≥ .18]). Similarly, there was no consistent pattern of difference between groups for postprandial total GLP‐1, acylated ghrelin and subjective appetite perceptions. Conclusions: In people with T2D and overweight or obesity, changes in postprandial appetite‐regulatory gut peptides may not underpin the less than predicted weight loss observed with empagliflozin therapy. Clinical Trials Registration: NCT02798744, www.ClinicalTrials.gov ; 2015‐001594‐40, www.EudraCT.ema.europa.eu ; ISRCTN82062639, www.ISRCTN.org .